Effect of local anaesthetic infiltration on chronic postsurgical pain after total hip and knee replacement: the APEX randomised controlled trials. Issue 6 (June 2015) - Wylde, Vikki; Lenguerrand, Erik; Gooberman-Hill, Rachael; Beswick, Andrew D.; Marques, Elsa; Noble, Sian; Horwood, Jeremy; Pyke, Mark; Dieppe, Paul; Blom, Ashley W.
Abstract : Abstract: Total hip replacement (THR) and total knee replacement (TKR) are usually effective at relieving pain; however, 7% to 23% of patients experience chronic postsurgical pain. These trials aimed to investigate the effect of local anaesthetic wound infiltration on pain severity at 12 months after primary THR or TKR for osteoarthritis. Between November 2009 and February 2012, 322 patients listed for THR and 316 listed for TKR were recruited into a single-centre double-blind randomised controlled trial. Participants were randomly assigned (1:1) to receive local anaesthetic infiltration and standard care or standard care alone. Participants and outcomes assessors were masked to group allocation. The primary outcome was pain severity on the WOMAC Pain Scale at 12 months after surgery. Analyses were conducted using intention-to-treat and per-protocol approaches. In the hip trial, patients in the intervention group had significantly less pain at 12 months postoperative than patients in the standard care group (differences in means: 4.74; 95% confidence interval [CI]: 0.95-8.54; P = 0.015), although the difference was not clinically significant. Post hoc analysis found that patients in the intervention group were more likely to have none to moderate pain than severe pain at 12 months than those in the standard care group (odds ratio: 10.19; 95% CI: 2.10-49.55; P = 0.004). In the knee trial, there was no strong evidence that the intervention influenced pain severity at 12 months postoperative (difference in means: 3.83; 95% CI: −0.83 to 8.49; P = 0.107). In conclusion, routine use of infiltration could be beneficial in improving long-term pain relief for some patients after THR. Abstract : Supplemental Digital Content is Available in the Text.Intraoperative local anaesthetic infiltration can reduce chronic postsurgical pain at 1 year after total hip replacement.